Effects of therapy with local anesthetics (TLA) on heart rate variability (HRV) over 24 hours - Weinschenk, Stefan; Topbas-Selcuki, Nurat Fitnat; Benrath, Justus; Strowitzki, Thomas; Feißt, Manuel (Chronobiology international, 2025)
Local anesthetics (LAs) are frequently used in regional anesthesia based on their properties to inhibit pain perception by blocking voltage-gated sodium channels (VGSC). In addition to this well-kn...